Primary Refractory Catastrophic Antiphospholipid Syndrome Masquerading as Buerger’s Disease - Tannous, Toufic (Cureus, 2021)
Catastrophic antiphospholipid syndrome (CAPS) is a lethal disease with up to 30% mortality rate. It can occur as a primary disease or secondary to an underlying autoimmune disease. Current treatment focuses on disease control with anticoagulation and steroids. Plasma exchange and intravenous immunoglobulin (IVIG) have shown some benefit when added. Monoclonal drugs such as rituximab have shown some benefit in refractory cases, and eculizumab, a drug approved for use in atypical hemolytic uremic syndrome, has demonstrated disease control in a few case reports. We describe a unique case of primary refractory CAPS with an unusual presentation that was treated with five lines of therapy before disease control was established.